p -type transparent conductor: Zn-doped CuAlS2 - Liu, Min-Ling; Huang, Fu-Qiang; Chen, Li-Dong; Wang, Yao-Ming; Wang, Ying-Hua; Li, Gui-Feng; Zhang, Qun (Applied physics letters, 2007)
A series of Zn-doped CuAlS2 bulk samples was synthesized by spark plasma sintering, and the CuAl0.90Zn0.10S2 film was prepared on a glass substrate by channel spark ablation. Their electrical and optical properties were carefully investigated. A sharp increase in conductivity due to the enhancement of both Hall mobility and carrier concentration was observed with the introduction of Zn. p-type conduction was confirmed by both the positive Seebeck coefficient and Hall coefficient. The conductivity of the thin film is as high as 63.5Scm−1 at room temperature, and the average transmittance in the visible region is above 80%.